Production Process of Traditional Ship in Bintan-Indonesia - Putra, Risandi Dwirama; Koto, J. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
Indonesia is the world's largest archipelagic country in the world, demand for marine transportation is very important. Marine transport being very strategic because it plays a role in connecting one island to another island and marine transport is a tool for economic activity. Global industrialisation causes traditional shipyard less competitive, causing reduction in the number of traditional ships, which are urgently needed to support economic activity. Proper production management planning at the shipyard is expected to help improve the quality of traditional shipbuilding for competitive. This paper discusses current issues of traditional shipyards in Kepulauan Riau-Indonesia and implementation of IDEF models as tool for solving the problem by taking the following factors into account: concept design, perform preliminary design, contract design, detail design and building of ships.